An Empirical Study Identifying the Most Favored Foreign Direct Investment Inflows Destination in the Gulf Cooperation Council Countries - Fernandez, Manuel; Joseph, Robinson; Fernandez, Vania Maria (International Journal of Economics and Financial Issues, 2023)
This study aims to identify the most favored foreign direct investment destination in the Gulf Cooperation Council countries. The study compares the global rankings of each GCC country on investment decision parameters: market size, economic growth, infrastructure, technology adoption, innovation friendliness, productive and diversified labor force, financial infrastructure, taxation, political risk, corruption, and ease of doing business. This study confirms that the UAE is the most favored FDI destination in the GCC. Moreover, the current policies and regulations promulgated indicate the country’s intent to become more investor-friendly and attractive to live in.